A Phenotype and Genotype Case Report of a Neonate With Congenital Bilateral Coronary Artery Fistulas and Multiple Collateral Arteries - Su, Shixin; Xia, Shuliang; He, Ye; Li, Jianbin; Ma, Li; Chen, Xinxin; Li, Jia (Frontiers in Cardiovascular Medicine, 2022)
We report a unique case of an 18-day-old girl with 3 coronary artery fistulas to the right atrium and right ventricle respectively, 3 collateral arteries arising from the descending aorta and 1 from the right subclavian artery draining through a sac to the top of the right atrium, patent ductus arteriosus and atrial septal defect. She presented symptoms of acute congestive heart failure. Cardiac catheterization and surgical interventions were performed to repair the defects. The patient recovered uneventfully and grew up well at 3 years follow-up. Whole genome sequencing in the patient, compared to her parents, showed 17 variants within 11 genes. Among these, only compound heterozygous mutation, c.T470G (p.L157R) and c.A1622G (p.D541G), in the DRC1 gene have been reportedly related to congenital heart disease and are the most likely causative in our patient.